H19 suppresses the growth of hepatoblastoma cells by promoting their apoptosis via the signaling pathways of miR‐675/FADD and miR‐138/PTK2. Issue 4 (26th October 2018) - Ge, Lili; Zhang, Xianwei; Hu, Shengnan; Song, Yinsen; Kong, Jinghui; Zhang, Bo; Yang, Xiaoang
Abstract: Background: The objective of this study was to clarify the molecular pathways involved in hepatitis B virus (HBV)‐induced hepatoblastoma. Method: The expression of factors in different signaling pathways (H19, miR‐675, miR‐138, protein tyrosine kinase 2 [PTK2], fas‐associated death domain [FADD], hypoxia‐inducible factor 1‐alpha [HIFIA], focal adhesion kinase [FAK], caspase‐8, and caspase‐3) was compared between HBV (+) and HBV (−) groups using quantitative real‐time polymerase chain reaction and Western blot analysis. Subsequently, immunohistochemistry (IHC) and TdT‐mediated dUTP Nick‐End Labeling (TUNEL) assays were used to verify the expression of above proteins in HBV (+) and HBV (−) groups. Computational analysis was conducted to predict the target genes of miR‐675 and miR‐138, whose regulatory relationships were then clarified using luciferase assays and cell transfection studies. Result: The expression of H19, miR‐675, PTK2, HIFIA, and FAK was increased in the HBV (+) group, while the expression of miR‐138, FADD, caspase‐8, and caspase‐3 was decreased in the HBV (+) group. FADD and PTK2 were identified as target genes of miR‐675 and miR‐138, respectively. In addition, miR‐675 was upregulated while miR‐138 was downregulated by X protein (HBx). Conclusion: In summary, the results of this study revealed the molecular pathways involved in HBV‐induced hepatoblastoma. In the presence of HBV, HBX upregulated the expression of H19 through HIFIA. Consecutively, overexpressed H19 upregulated the expression of PTK2 via targeting miR‐138 and downregulated the expression of FADD via targeting miR‐675. Finally, increased expression of PTK2 and reduced expression of FADD both led to the inhibition of cell apoptosis, thus promoting the tumorigenesis of hepatoblastoma. Abstract : In the presence of hepatitis B virus (HBV), X protein (HBX) upregulated the expression of H19 through HIFIA. Consecutively, overexpressed H19 upregulated the expression of PTK2 via targeting miR‐138 and downregulated the expression of fas‐associated death domain (FADD) via targeting miR‐675. Finally, increased expression of PTK2 and reduced expression of FADD both led to the inhibition of cell apoptosis, thus promoting the tumorigenesis of hepatoblastoma.